PLASMA LEVEL OF NOREPINEPHRINE, CYCLIC AMP AND CYCLIC GMP IN ESSENTIAL HYPERTENSION - OGAWA, KOUICHI; MATSUNO, TSUGUO; TSUCHIYA, SEIYA; BAN, MASAAKI; MINAGUCHI, KAZUE (JAPANESE CIRCULATION JOURNAL, 1981)
Mean concentration of plasma norepinephrine of 66 normal subjects was 0.23 ± 0.02 ng/ml, but that of 81 hypertensives was 0.25 ± 0.02 ng/ml. There was no significant difference of plasma norepinephrine concentration between the normotensives and the hypertensives. However, a significant correlation was demonstrated between the concentration of norepinephrine and age in the normotensives (r = 0.51, p<0.001). Nonetheless, this correlation was not found in the group with essential hypertension. Age matching revealed a significant higher concentration of norepinephrine in the twenties and the thirties and no significant difference in the forties and the fifties. There was also significant negative correlations between the concentration of norepinephrine and both the percent changes in mean blood pressure (r = -0.31, p<0.01) and the percent changes in diastolic pressure (r = -0.32, p<0.005) after twenty minutes in the recumbent position in the clinic. Mean concentration of plasma cyclic AMP and cyclic GMP of 70 normal subjects were 17.7 ± 0.4 pmol/ml and 4.3 ± 0.02 pmol/ml respectively. There was a significant correlation between the concentration of plasma cyclic GMP and age (r = 0.30, p<0.001), and no correlation between the concentration of cyclic AMP and age in normal subjects. Mean concentration of plasma cyclic AMP of 68 hypertensives was 25.0 ± 0.8 pmol/ml and significantly higher than normal subjects (p<0.001 ). But, that of cyclic GMP of the same patients was 4.4 ± 0.2 pmol/ml and there was no significant difference between the normotensives and the hypertensives. Thus, it was suggested that sympathetic nervous activity was not elevated in older patients with essential hypertension but was elevated in younger patients and that the second messenger system of cyclic AMP was augmented in all patients with essential hypertension.